Personality Development in Emerging Adulthood—How the Perception of Life Events and Mindset Affect Personality Trait Change - De Vries, Jantje Hinrika; Spengler, Maik; Frintrup, Andreas; Mussel, Patrick (Frontiers in Psychology, 2021)
Personality changes throughout the life course and change is often caused by environmental influences, such as critical life events. In the present study, we investigate personality trait development in emerging adulthood as a result of experiencing two major life events: graduating from school and moving away from home. Thereby, we examined the occurrence of the two life events per se and the subjective perception of the critical life event in terms of valence. In addition, we postulate a moderation effect of the construct of mindset, which emphasizes that beliefs over the malleability of global attributes can be seen as predictors of resilience to challenges. This suggests that mindset acts as a buffer for these two distinct events. In a large longitudinal sample of 1,243 people entering adulthood, we applied latent structural equation modeling to assess mean-level changes in the Big Five, the influence of life events per se, the subjective perception of life events, and a moderating role of mindset. In line with maturity processes, results showed significant mean-level changes in all Big Five traits. While no changes in the Big Five dimensions were noted when the mere occurrence of an event is assessed, results indicated a greater increase in extraversion and diminished increase in emotional stability when we accounted for the individual’s (positive/ negative) perception of the critical life event. In case of extraversion, this also holds true for the moderator mindset. Our findings contribute valuable insights into the relevance of subjective appraisals to life events and the importance of underlying processes to these events.